Synthesis and antifungal potential of 1,2,3-triazole and 1,2,4-triazole thiol substituted strobilurin derivatives - Chaudhary, Preeti M.; Tupe, Santosh G.; Jorwekar, Shweta U.; Sant, Duhita G.; Deshpande, Sunita R.; Maybhate, Shailaja P.; Likhite, Anjali P.; Deshpande, Mukund V. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2015)
beta-Methoxyacrylate group is an important pharmacophore of commercially used strobilurin fungicides. In the present study, a total of seventeen 1,2,4-triazole thiols 8a-h and 1,2,3-triazole substituted 10a-i strobilurin derivatives have been synthesized. 1,2,4-Triazole thiol substituted strobilurin derivatives 8a-h have been found to inhibit the growth of plant pathogens such as Fusarium oxysporum, Magnaporthe grisea, Drechslera oryzae and human pathogens Aspergillus fumigatus and different strains of Cryptococcus neoformans, with MIC in the range of 16-256 mu g/mL. In case of Candida albicans tested strain, the MIC is > 256 mu g/mL. p-Chlorophenyl substituted 1,2,4-triazole thiol strobiulrin derivative 8e is the most potent inhibitor with MIC of 16-64 mu g/mL against most of the tested pathogens. Antifungal action of the compounds is due to inhibition of mitochondrial respiration. In the resazurin reduction assay, EC50 for inhibition of RZ reduction in D. oryzae by azoxystrobin and 8e are 3.42 +/- 0.03 mu g/mL and 3.63 +/- 0.21 mu g/mL, respectively; while in case of C. neoformans, EC50,, of azoxystrobin and 8e are between 0.65-0.85 mu g/mL. In a non-pathogenic model Benjaminiella poitrasii, though the MIC for all the synthesized compounds 8a-h and 10a-i are > 256 mu g/ml, yeast to hypha transition is inhibited in the range of 21-75% at 4 mu g/mL concentration while EC50 for inhibition of RZ reduction by azoxystrobin and 8e are 31.5 +/- 0.4 mu g/mL and 17.95 +/- 0.7 mu g/mL, respectively. The 50% germ tube formation inhibition in case of C. albicans is observed at 108.49 mu g/mL. 1,2,4-Triazole thiol substituted strobilurin derivatives hold promise for the control of pathogenic fungi in agriculture and health care.
Keywords: 1; 2; 3-triazole strobilurin; 4-triazole thiol strobilurin; antifungal; Strobilurin; Y-H transition inhibition